Analisis Genangan Air di Kampung Sudika Indah Kecamatan Tarogong Kidul Kabupaten Garut - Lukman Rudiat; Sulwan Permana (Institut Teknologi Garut, 2026)
Flooding, or what is often referred to as flooding, is a very common disaster in Indonesia. There is a case in a residential area near the Cimanuk River, namely in Kampung Sudika Indah RT 02 RW 13, Tarogong Kidul District, Garut Regency. Flooding often occurs, which is thought to be caused by the drainage system, so that the water discharge and high rainfall intensity over a long period of time cannot be accommodated and drained to the outlet. This is one of the main factors contributing to flooding. Therefore, research is needed on what has happened so that the incident can be evaluated and a solution found. The purpose of this study is to analyze the dimensions of the drainage channels in Kampung Sudika Indah. In this study, the method used is to process the maximum rainfall using the Log Pearson Type III method, then test it using the Chi-Square and Smirnov-Kolmogorov methods. Next, calculate the 10-year rainfall intensity. Simulation was carried out using the SWMM application. The SWMM application summary results showed that water overflow occurred in channel 4. The overflow occurred in channel 4, which had a peak overflow volume of 11.107 m3/sec with a duration of 1.20 hours. Therefore, based on the results of trials by changing the channel dimensions, it can be concluded that channel 4 requires an increase in the existing cross-sectional dimensions from 2.5 m x 2 m to 3.5 m x 2 m.